Perception of the threat, mental health burden, and healthcare-seeking behavior change among psoriasis patients during the COVID-19 pandemic. - Hsien-Yi Chiu; Nien-Feng Chang Liao; Yu Lin; Yu-Huei Huang (PLoS ONE)
This study aimed to investigate the perceived threat, mental health outcomes, behavior changes, and associated predictors among psoriasis patients during the COVID-19 pandemic. The COVID-19 has been known to increase the health risks of patients with psoriasis owing to patients' immune dysregulation, comorbidities, and immunosuppressive drug use. A total of 423 psoriasis patients not infected with COVID-19 was recruited from the Department of Dermatology, National Taiwan University Hospital Hsin-Chu Branch, Chang Gung Memorial Hospital, and China Medical University Hospital from May 2020 to July 2020. A self-administered questionnaire was used to evaluate the perceived threat, mental health, and psychological impact on psoriasis patients using the Perceived COVID-19-Related Risk Scale score for Psoriasis (PCRSP), depression, anxiety, insomnia, and stress-associated symptoms (DAISS) scales, and Impact of Event Scale-Revised (IES-R), respectively. Over 94% of 423 patients with psoriasis perceived threat to be ≥ 1 due to COVID-19; 18% of the patients experienced psychological symptoms more frequently ≥ 1, and 22% perceived psychological impact during the pandemic to be ≥ 1. Multivariable linear regression showed that the higher psoriasis severity and comorbidities were significantly associated with higher PCRSP, DAISS, and IES-R scores. The requirement for a prolonged prescription and canceling or deferring clinic visits for psoriasis treatment among patients are the two most common healthcare-seeking behavior changes during the COVID-19 pandemic. Psoriasis patients who perceived a higher COVID-19 threat were more likely to require a prolonged prescription and have their clinic visits canceled or deferred. Surveillance of the psychological consequences in psoriasis patients due to COVID-19 must be implemented to avoid psychological consequences and inappropriate treatment delays or withdrawal.